Primeiro copiador de respostas dos senhores governadores (Ms. PBA-479, Biblioteca Nacional de Portugal) (1710-1721): estudo das abreviaturas e edição - Christiane Benones de Oliveira (2023)
The use of abbreviations is vastly common, which causes great difficulty when reading this type of documents. Therefore, in order to contribute to the studies of other researchers in the future, we aim to fill up some gaps regarding the theme. For this purpose, the chosen corpus is the manuscript entitled Primeiro copiador das respostas dos senhores governadores desta capitania [minas gerais] às ordens de s[u]a mag[esta]de, e contas que lhe derão que principia no governo do sen[h]or Antonio de Albuquerque Coelho de Carvalho. The document was written between the years of 1710 and 1721, has 120 front and back folios, and is available online on the website of the National Digital Library of Portugal. The research is developed in three parts: the diplomatic edition of the document, the description of the total abbreviations collected from the manuscript and the analysis of the abbreviations by superscript letters present in the text. From this study, it was possible to detect some patterns in the process of overwriting the abbreviations analyzed. The research is based on bibliographic and interpretive research methods.